Karakteristik Pemegang Amânah dalam Al-Qur’an - Halim, Abdul; Zulheldi, Zulheldi; Sobhan, Sobhan (Universitas Islam Negeri Imam Bonjol Padang, 2019)
There are three important components in amâna. Of course amâna itself, giver and receiver or holder. Man is an ultimate receiver in amâna. However, not all can maintain and fulfill amâna but also a competent holder of amâna who have doing this. By using the maudhû’i method and content analysis approach, research on the story of the Prophet Josef, Moses and Thalut produced three classification of characteristics that must be owned by the holder of amâna, that is spiritual characteristics, operational characteristics and emotional characteristics.